Sensory-motor responses in fencing - Czajkowski, Z. (Studies in Physical Culture and Tourism, 2011)
All branches of sport share many common traits and also feature many different characteristics. Some sports feature only one closed (intrinsic) sensory-motor skill (weightlifting, field-and-track events), no direct opponent and no tactics. Other sports involve many closed (intrinsic) sensory-motor skills (figure skating, artistic gymnastics), no direct opponent and no tactics. The accuracy and beauty of predicted movements in those sports are assessed by the judges. Fencing and other combat sports, sports games and team games differ considerably in the above respect in having many open (extrinsic) sensory-motor skills, facing directly the opponent, and great importance of tactics. In fencing, it is not only important how to execute a given fencing action (sensory-motor skill), but also how to apply a chosen action in a bout. Technical-tactical and tactical abilities are of immense significance here. In fencing, sensory-motor skills, i.e. various fencing actions (offensive, defensive, and counter-offensive), are mostly applied in a bout as different types of sensory-motor responses: simple, choice, differential, sensory-motor responses to a pre-signal, sensory-motor response to a moving object, switch-over responses (changes of decision while executing a foreseen action) and intuitive responses.